A pilot study of new approaches to exploring illness trajectories and patterns of comorbidity in major mental disorders. Issue 8 (23rd November 2021) - Scott, Jan; Vorspan, Florence; Loftus, Josephine; Bellivier, Frank; Etain, Bruno
Abstract: Aims: We explored lifetime comorbidities in clinical subsamples with a diagnosis of Psychosis ( N = 143), bipolar (BD = 511), and unipolar disorders (UP = 861). Methods: We analyzed trajectories and patterns of comorbidities using novel metrics, namely bubble plots and density of antecedent events per year of illness exposure per individual. Results: Age at onset (AAO) of most comorbidities was similar to epidemiological studies, but cumulative rates were higher in clinical cases. There were some between group differences in patterns or burden of comorbidities, for example, Psychosis showed the earliest AAO of any mental disorder; UP showed the latest AAO of the index diagnosis. The relative risk of multimorbidity was lower in UP compared with other diagnoses, however, the goodness of fit for the illness trajectory path was lowest for BD. Conclusions: Bubble plots offer a useful representation of timing, sequence, cumulative probability and of comorbidities, the added value of reporting density measures was less obvious.